Midwife’s Role in The Implementation of The Health Minister’s Regulation Number 66 of 2014 Through Stimulation, Early Detection and Intervention Activities to Child’s Growth Disruption at Public Health Centers of Yogyakarta City - Ni Luh Gede Wira Yanti; Endang Widyorini; Bernadeta Resti Nurhayati (Universitas Katolik Soegijapranata Semarang, 2019)
Every child had the rights to survive, grow, and well develop to perfect adulthood.However, many children with special needs were factually ignored by their families even theywere often considered as family’s disgrace. The government, through midwives, could play arole in minimising the risks experienced by children with special needs by doing stimulation,early detection and intervention to child’s growth disruption.This research usedsocio‐legal approach with the analytical‐descriptive specification. Primarydata were obtained from interviews with Head of Health Centers (Puskesmas) of Mergangsan,Jetis and Tegalrejo beside with midwives, integrated service post (posyandu) cadres, and fiveparents of children with special needs. Secondary data were obtained from books and legalmaterials related to the research. The data were then qualitatively analysed.The results showed that the three Health Centers (Puskesmas), namelyMergangsan, Jetis andTegalrejo, had implemented the Health Minister’s Regulation Nr. 66 of 2014. The HealthCenters had programs having relations with child’s growth that was SDIDTK (stimulation, earlydetection and intervention of growth disruption). Midwives had performed their roles instimulation, early detection and intervention of growth disruption thorough examination thatwas monthly conducted together with posyandu’s activities at the Health Centers.Supporting factors of the monitoring implementation of a child’s growth, development anddevelopment disruption included health care facilities, adequate human resources (healthworkers), affordable posyandu’s costs and cross‐sectorial cooperation. The inhibiting factorswere low‐income family’s supports, unfavourable social and economic conditions and mother'sknowledge that remained poor.